From an international English language assessment framework to a teacher-based assessment: A study of primary English teachers’ agentive perspectives and projections - Santi Farmasari (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2021)
This study explores four primary English teachers' agentive perspectives about assessment in their schools. Given the challenges brought by the abolition of International Standard School (ISS), the changed status of the school, and the exclusion of English from the 2013 National Education Curriculum (NEC), a teacher-based assessment was the only solution to the unavailability of assessment guidelines and the unsuitability of assessment materials and methods. Employing teacher agency theory, this study examines the agentive sides of the teachers' perspectives as they would represent the teachers' strategic solutions toward the school's emerging problems. The teacher-based assessment was expected to accommodate the school's context, the students, and the subject taught. This instrumental case study's data was collected through semi-structured interviews and focus group discussion, which was then analyzed through six phases of thematic analysis and by employing nVivo12 software. The study indicates that the challenges brought by the changed educational policies reinforced collaborative work amongst the teachers. The teachers' perspectives also represent their agentive projections toward English language assessment which was heavily shaped by the teachers' previous assessment experiences during ISS and their ultimate teaching objectives. The findings are expected to provide insightful knowledge about how English teachers responded to shifted educational policies and projected to accommodate the school's specific contexts of assessment. The findings are also expected to explain how people's perspectives can be examined from an agency perspective.